Simulation and economic analysis of the high-temperature heat storage system of thermal power plants oriented to the smart grid - Zhang, Hongwei; Zhao, Mingyuan; Li, Yanbing; Liu, Junqing; Liang, Wenbin (Frontiers in Energy Research, 2023)
With the continuous increase of the grid-connected proportion of intermittent renewable energy, in order to ensure the reliability of smart grid operation, it is urgent to improve the operational flexibility of thermal power plants. Electric heat storage technology has broad prospects in terms of in-depth peak shaving of power grids, improving new energy utilization rates, and improving the environment. It is an important means to promote electric energy substitution. The economics of technical application scenarios are compared and analyzed, the principle of solid heat storage technology is discussed, and its application in heating fields such as industrial steam, district heating and deep peak regulation of congeneration units is expounded. In the scenario where the peak shaving subsidy and the heat storage duration are the same, as the unit output increases, the investment recovery period increases.The power market peak shaving subsidy has a great impact on the investment recovery period. In the 0.3 yuan/kW power market peaking subsidy scenario, only when the unit output is 0 and the heat storage time is greater than 8 hours, the investment can be recovered in 5 years, while in the 0.7 yuan/kW power market peaking subsidy scenario, Except for the scenario where the unit output is 40% and the heat storage time is 7h, the investment cannot be recovered, in other scenarios, the investment can be recovered within 5 years.